PERIPETEIAS OF FASHION: FROM CHANGE OF STAGES TO ANTHROPOGENIC MEANINGS - Ushakova, Y. A. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2017)
The article is devoted to the study of the fashion cycle, its stages and to the revealing of corresponding anthropogenic meanings. Actuality of this approach is conditioned by theoretical contradictions in the study of fashion, heterogeneous, mutually exclusive definitions of this phenomenon. The purpose of this article is the consideration of the fashion cycle as a basis for the subsequent unification of the scientific notion about this fundamental and at the same time underestimated phenomenon of culture. A detailed analysis of the stages and transitions in the development of the fashion cycle promotes the recognition of fashion in the unity of its particular and general manifestations. Each stage and periods of transformations have their own anthropologically significant meanings. As a result of this approach, the opportunity opens up for a practical understanding of the importance of fashion and the fashion process in shaping the life of culture. Full scientific understanding of fashion allows clearing up the peculiarities of its influence on the laws of development of the anthroposphere.